Legal Review of LGBT Practices from a Human Rights Perspective Within Indonesian Law - Rovy Igvirly; Wendra Yunaldi (Fakultas Hukum Universitas Djuanda, 2025)
Deviant sexual behavior by LGBT (Lesbian, Gay, Bisexual, and Transgender) groups, which initially developed in Western countries, has also emerged in Indonesia in recent years. This phenomenon raises legal, moral, and religious concerns in a society that upholds Pancasila values. This study uses a normative juridical approach by analyzing laws, literature, journals, and online sources to examine the legal framework related to LGBT issues in Indonesia. The study finds that while human rights are recognized in the Indonesian Constitution, they are limited by morality, religion, and public order. The existence of LGBT is considered contrary to these values. Same-sex marriage is not justified under Indonesian law, which defines marriage as a union between a man and a woman. LGBT behavior is viewed as a deviant act that must be addressed by the state to protect societal values and legal norms. The government is encouraged to implement treatment and rehabilitation policies rather than recognition or legalization of LGBT practices, in order to maintain national identity rooted in moral and religious values.